Let's Investigate Art: Places in Art - Gogerty, Clare (Marshall Cavendish Corporation, 1995)
Each title in this practical art series is designed to help readers enjoy and understand works of art, while encouraging them to create their own. Highly illustrated, with fact boxes and activities, the series should be suitable as an introduction to the world of art and the inspiration behind it.
Keywords: Art; History; Juvenile Nonfiction